2018
DOI: 10.1177/0032258x18768397
|View full text |Cite
|
Sign up to set email alerts
|

Keeping an eye on the neighbours: Police, citizens, and communication within mobile neighbourhood crime prevention groups

Abstract: Mobile neighbourhood crime prevention has become increasingly popular in the Netherlands. Since 2015, 7,250 WhatsApp neighbourhood crime prevention (WNCP) groups have been registered online, most of which are initiated and moderated by citizens. This entails a form of participatory policing aimed at neighbourhood crime prevention, which may provoke increased feelings of anxiety and interpersonal surveillance. Community police officers and citizens need to adapt to changed interactions and trust relations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Other research has highlighted the successful communitybased social media systems. For instance, WhatsApp neighborhood crime prevention group [27] was initiated by citizens in the Netherlands to empower social control and increase social cohesion and collective efficacy…”
Section: Related Workmentioning
confidence: 99%
“…Other research has highlighted the successful communitybased social media systems. For instance, WhatsApp neighborhood crime prevention group [27] was initiated by citizens in the Netherlands to empower social control and increase social cohesion and collective efficacy…”
Section: Related Workmentioning
confidence: 99%
“…Research in this context has shown how these groups can lead to a (temporary) decrease in break-ins (Akkermans and Vollaard 2015) and can further social cohesion in local communities (van der Land, van Stokkom, and Boutellier 2014). However, WNCP groups can also lead to the displacement of criminality (van der Land, van Stokkom, and Boutellier 2014), raise privacy concerns (Pridmore, Mols, Wang, and Holleman 2019;de Vries 2016), and increase discriminatory practices and feelings of anxiety (Lub 2016).…”
Section: Articlementioning
confidence: 99%
“…When citizens actively monitor their streets, record events, and report about suspicious situations or persons, they are informally taking over police duties. Citizen policing (a term which is interestingly not directly translatable to Dutch, see Pridmore et al 2019) raises questions about accountability and responsibility. Mobilised citizens may act as "embodied surveillance units" (Larsen and Piché 2010: 197) who become responsible for the security of themselves and others, but can they also be held accountable when their safeguarding practices fail or a dangerous situation escalates?…”
Section: Reageren: React In a Safe Mannermentioning
confidence: 99%
“…The level of public confidence in the police will identify the effectiveness of its work. Police and community need to adapt to changing interactions and improve communication in an effort to increase cooperation in ensuring community safety (Pridmore et al, 2019).…”
Section: Introductionmentioning
confidence: 99%